ECHOCARDIOGRAPHIC AND LABORATORY MARKERS OF CHRONIC HEART FAILURE: WHETHER IT IS POSSIBLE TO USE THEM IN RHEUMATIC MITRAL DISEASES? - T. A. Kazakovtseva; N. A. Shostak (Рациональная фармакотерапия в кардиологии)
Aim. To find echocardiographic indicators of heart remodelling that improve estimation of heart failure (HF) severity. To evaluate sensitivity of laboratory markers of HF, brain (BNP) and atrial (ANP) natriuretic peptides, in patients with mitral heart diseases of rheumatic aetiology.Material and methods. 100 patients with rheumatic mitral disease and chronic HF (CHF) of I-IV class (NYHA) were examined. Echocardiography was performed in all patients with evaluation of the standard indices to define disease severity. Indices of sphericity, myocardial stress of the left ventricle, etc were also evaluated. BNP and ANB levels were assessed by enzyme immunoassay method.Results. CHF severity had the strongest correlations with atrial sizes, left atrial systolic function and level of pulmonary hypertension. Moderate increase of BNP level in severe CHF (III-IV class) and its rare increase in mild CHF (I-II class) were detected. Significant changes of ANP level were not found. Moderate correlation of BNP level with myocardium mass index, level of pulmonary hypertension and mitral regurgitation was detected.Conclusion. Intensity of heart remodelling in rheumatic mitral diseases is mainly determined by the left atrial area, left atrial systolic function, mitral orifice size, levels of mitral regurgitation and pulmonary hypertension, size and ejection fraction of right ventricle. Normal BNP level does not confirm an absence of CHF or negative prognosis in patients with rheumatic heart disease.